Penanaman Nilai-Nilai Pendidikan Islam Pada Anak Yatim dan Dhuafa Melalui Pendidikan Luar Sekolah - Muhammad Farikhin; Abdul Muhid (STAIN Bengkalis, 2022)
This article examines the inculcation of Islamic educational values to orphans and poor people through out-of-school education. Cultivating values is an effort to instill values or traits that become the basis of behavior in everyday life. The writing of this article is in the form of a literature review using content analysis techniques. This writing aims to increase the reader's insight about education outside of school as an institution that becomes a forum for instilling Islamic educational values to orphans and poor people. The cultivation of Islamic educational values can be interpreted as a process of inculcating values whose all aspects are based on Islamic teachings that are sourced from the Qur'an and the hadith of the Prophet. The values given to orphans and poor people are intended so that they can know, master and believe in the values of Islamic education. The form of internalization of Islamic educational values includes the cultivation of faith values, worship values, and moral values. These values must be implemented and applied in everyday life by setting a good example for orphans and poor people._____________________Keywords: islamic education, orphans and dhuafa, education outside school.